Theoretical and practical development of the TOPSY self-management intervention for women who use a vaginal pessary for pelvic organ prolapse - Lucy Dwyer; Carol Bugge; Suzanne Hagen; Kirsteen Goodman; Wael Agur; Melanie Dembinsky; Margaret Graham; Karen Guerrero; Christine Hemming; Aethele Khunda; Doreen McClurg; Lynn Melone; et al. (Trials, 2022)
Abstract Background Pelvic organ prolapse (POP) is a common condition in women, where the downward descent of pelvic organs into the vagina causes symptoms which impacts quality of life. Vaginal pessaries offer an effective alternative to surgery for the management of POP. However, the need for regular follow-up can be burdensome for women and requires significant healthcare resources. The TOPSY study is a randomised controlled trial which aims to determine the clinical and cost-effectiveness of self-management of vaginal pessaries. This paper describes the theoretical and practical development of the self-management intervention. Methods The intervention was developed using the MRC complex intervention framework, normalisation process theory (NPT) and self-management theory. The intervention aims to boost perceived self-efficacy in accordance with Bandura’s social cognitive theory and is guided by the tasks and skills Lorig and Hollman describe as necessary to self-manage a health condition. Results The TOPSY intervention was designed to support women to undertake the medical management, role management and emotional management of their pessary. The six self-management skills described by Lorig and Hollman: problem-solving, decision-making, resource utilisation, formation of a patient-provider partnership role, action planning and self-tailoring, are discussed in detail, including how women were supported to achieve each task within the context of pessary self-management. The TOPSY intervention includes a self-management support session with a pessary practitioner trained in intervention delivery, a follow-up phone call 2 weeks later and ongoing telephone or face-to-face support as required by the woman initiated by contacting a member of the research team. Conclusions The TOPSY study intervention was developed utilising the findings from a prior service development project, intervention development and self-efficacy theory, relevant literature, clinician experience and feedback from pessary using women and members of the public. In 2022, the findings of the TOPSY study will provide further evidence to inform this important aspect of pessary management. Trial registration ISRCTN Registry ISRCTN62510577 . Registered on June 10, 2017